PENGARUH KUALITAS SUMBER DAYA MANUSIA, PEMANFAATAN TEKNOLOGI INFORMASI DAN SISTEM PENGENDALIAN INTERNAL TERHADAP KEANDALAN PELAPORAN KEUANGAN PEMERINTAH DESA DI KECAMATAN RAMBAH - Dahlia (Hirarki : Jurnal Ilmiah Manajemen dan Bisnis, 2023)
This study aims to determine whether the quality of human resources, the use of information technology and internal control systems affect the reliability of village government financial reporting in Rambah District. The population of this study is all village officials in the Rambah District, namely 94 people. Sampling method using saturated sampling (census) with a total of 94 people. The analysis technique used is multiple linear regression analysis using the SPSS 18 program. The results of the research based on multiple linear regression analysis show that: (1) the quality of human resources has a positive and significant effect on the reliability of village government financial reporting in Rambah District with a coefficient of 0.822, (2) the use of information technology has a positive and significant effect on the reliability of village government financial reporting in Rambah District with a coefficient of 0.112, (3) the internal control system has a positive and significant effect on the reliability of village government financial reporting in Rambah District with a coefficient of 0.584. The conclusion of this study is based on the results of partial testing only variables, namely the quality of human resources and internal control systems which have a positive and significant effect on the reliability of village government financial reporting in Rambah District, while simultaneously the quality of human resources, utilization of information technology and control systems internal influence on the reliability of village government financial reporting in Rambah District.